Influence of inhomogeneity of temperature time series on the estimation of regional climate changes - Osadchyi, V.I.; Skrynyk, O.A.; Skrynyk, O.Ya. (Reports of the National Academy of Sciences of Ukraine, 2017)
Based on a trend analysis of raw and homogenized temperature data, the influence of inhomogeneities of time series on the assessment of temperature changes in Ukraine has been studied. The raw monthly mean temperature data collected at 178 stations during the period 1946—2010 and respective homogenized data, which had been obtained in the Ukrainian Hydrometeorological Institute, have been used for the analysis. The analysis has revealed the substantial influence of “station signals” on the assessment of regional climate changes.